2021
DOI: 10.1136/bjophthalmol-2021-319090
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of brolucizumab versus aflibercept in eyes with polypoidal choroidal vasculopathy in Japanese participants of HAWK

Abstract: PurposeTo compare the efficacy and safety of brolucizumab versus aflibercept in eyes with polypoidal choroidal vasculopathy (PCV) over 96 weeks in the HAWK study.DesignHAWK was a global, 2-year, randomised, double-masked, multicentre phase III trial in participants with neovascular age-related macular degeneration.MethodsOf the Japanese participants with PCV, 39 received brolucizumab 6 mg and 30 received aflibercept 2 mg. After 3 monthly loading doses, brolucizumab-treated eyes received an injection every 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 18 publications
5
46
0
2
Order By: Relevance
“…In the current study, two (11.8%) of 17 eyes had IOI. The frequency of IOI was roughly the same compared with a sub-analysis of HAWK study which Ogura et al reported (15.4%) 15 17 . Although IVBr injections for PCV are effective, we should be cautious about IOI and treat promptly if brolucizumab-related IOI develops.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the current study, two (11.8%) of 17 eyes had IOI. The frequency of IOI was roughly the same compared with a sub-analysis of HAWK study which Ogura et al reported (15.4%) 15 17 . Although IVBr injections for PCV are effective, we should be cautious about IOI and treat promptly if brolucizumab-related IOI develops.…”
Section: Discussionsupporting
confidence: 70%
“…In a sub-analysis of the HAWK study, Ogura et al 17 reported the efficacy of brolucizumab in Japanese patients with PCV. They reported brolucizumab (n = 39) was as good as aflibercept (n = 30) in improving vision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After three monthly loading IVI of both brolucizumab 6mg/0.05mL dosed at 8 or 12 weeks and aflibercept 2mg/0.05mL dosed at 8 weeks, two separate Phase III clinical trials [HAWK (NCT02307682) and HARRIER (NCT02434328)] showed that brolucizumab was non-inferior to the comparative agent in terms of visual acuity for treatment-naïve neovascular age-related macular degeneration (AMD). [4][5][6][7] Brolucizumab has a potential for increased durability and is the first drug in its class to be authorized for, after three loading doses, a dosing interval range of 8 to 12 weeks. 6 This agent was granted approval on October 7, 2019, in the United States (US) by the Food and Drug Administration; following this, it gained approval for use in the European Union (EU) on February 17, 2020, by the European Commission.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Brolucizumab has a potential for increased durability and is the first drug in its class to be authorized for, after three loading doses, a dosing interval range of 8 to 12 weeks. 6 This agent was granted approval on October 7, 2019, in the United States (US) by the Food and Drug Administration; following this, it gained approval for use in the European Union (EU) on February 17, 2020, by the European Commission. 8 Using HAWK and HARRIER along with additional supportive safety data, provided by a Phase I (NCT01304693) and Phase II study (OSPREY; NCT01796964), brolucizumab underwent a systemic and ocular safety assessment.…”
Section: Introductionmentioning
confidence: 99%